PROBLEMS OF FORMATION OF RUSSIAN INNOVATIVE AGRICULTURAL TRACTORS FLEET - V. M. Kryazhkov; Z. A. Godzhaev; V. G. Shevtsov; S. G. Gurylev; A. V. Lavrov; A. N. Osherov (Сельскохозяйственные машины и технологии, 2015)
Formation of tractors park and its perspective development are carried out on the basis of realization and improvement of the scientifically based types range constructed on a traction classification sign which conforms to requirements of agricultural production when performing two main conditions: full meeting the requirements for various standard sizes of tractors applicable to conditions of the corresponding zones of Russia and continuous reproduction and development of tractor fleet, both by quantity of efficient machinery and its structure. The developed types range practically runs the gamut of organizational and economic and climatic conditions, and also all range of forms of the organizations using machinery, beginning from individual consumers, small and large rent and contract collectives and finishing large-scale enterprises and their associations. Federal Service of State Statistics (Rosstat) information about a steady tendency of fleet reduction was used for studying of regularities of development of tractor fleet. This information was added by analytical synthesis of data about the annual brand purchases in the Russian market of agricultural tractors. The developed database shows a share of the tractors in fleets of agricultural organizations, which are used over depreciation term, and also minimum necessary number of new machines introduction for formation of volume of tractors with limit age and the total quantity of tractors necessary for minimization of set of expenses. It was established that it is possible to estimate visually the developed quantitative and age structure of tractors fleet and to predict its development on prospect by worked out database representing set of annual tractors brand lines purchasing.